2012
DOI: 10.1177/0021998312437231
|View full text |Cite
|
Sign up to set email alerts
|

Critical compressive stress for continuous fiber unidirectional composites

Abstract: Dow and Rosen’s work in 1965 formed an intellectual framework for compressive strength of unidirectional composites. Compressive strength was explained in terms of micro-buckling, in which filaments are beams on an elastic foundation. While groundbreaking, the discrepancy between model predictions and observed compressive strength is well known. This study builds on Dow and Rosen’s model specifically with respect to the dominant shear mode instability. A new method that accounts for matrix thermal residual str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Thompson et al . 6 proposed the Combined Stress Model to estimate the compressive strength of unidirectional continuous fiber composites. Their approach incorporated a fiber misalignment cumulative distribution function (CDF), matrix nonlinearity, thermal prestress, fiber elastic properties, and fiber volume fraction.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thompson et al . 6 proposed the Combined Stress Model to estimate the compressive strength of unidirectional continuous fiber composites. Their approach incorporated a fiber misalignment cumulative distribution function (CDF), matrix nonlinearity, thermal prestress, fiber elastic properties, and fiber volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson et al . 6 also supplied variable sensitivity plots. Hypothetically, the model suggested that a glass-resin composite of identical constituents as the test case, but with perfect fiber alignment, would have a compressive strength of 1.3 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations